(untitled) (Homoeopathy for All, 2026)
Background: Urolithiasis is a common condition that accounts for a substantial number of hospital visits. It occurs when calculi form within the renal pelvis and subsequently migrate into other parts of the urinary collecting system, including the ureters, bladder and urethra. Case Summary: A case of a right lower ureteric calculus measuring 1.1 cm, associated with mild to moderate hydroureteronephrosis, along with a small left renal calculus, was identified on ultrasonography. The patient presented with pain in both inguinal regions and reported to the outpatient department of the Clinical Research Unit (Homoeopathy), Dimapur, Nagaland, on 18 September 2019. Based on the clinical presentation, individualized homoeopathic treatment was initiated with Lycopodium clavatum, followed by Berberisvulgaris Q. During the course of management, the patient was monitored clinically and through relevant investigations. Conclusion: This case documents the clinical course of ureteric calculus during homoeopathic management, in which expulsion of the stone was observed. As an individual case report, it does not establish causality and further systematic studies are required to evaluate outcomes in similar clinical conditions.